Navigating legal and social barriers: Labor market integration strategies of non-EU international students in Sweden - Amarasinghe Gunawardanalage Dona,Dewni (2025)
The thesis explores how non-EU international students at Lund University navigate the legal and social barriers encountered within the Swedish labor market while simultaneously pursuing their education. Although students are legally allowed to work during their studies, their experiences show a notable gap between formal employment rights and actual job opportunities. The study aims to investigate how students overcome these challenges through their job search strategies. Using a qualitative research design, the study is based on semi-structured interviews with seven international students and is analyzed using Bourdieu’s theory of capital, labor market segmentation theory, and discrimination theory to frame the analysis. The findings reveal that students encounter several legal and structural challenges, such as delays in obtaining a personal number, employer misunderstandings about visa-related work entitlements, and complex bureaucratic requirements. These structural barriers are further intensified by social barriers, including stringent language proficiency expectations, perceived discrimination, and the devaluation of non-Swedish qualifications. In response, students employ adaptive strategies such as networking, customizing job applications to align with employer expectations, engaging in internships or unpaid voluntary positions, and targeting accessible job sectors. The thesis concludes that legal entitlement to work, in isolation, is insufficient to ensure equitable labor market participation. Instead, meaningful inclusion necessitates social recognition, robust institutional support, and implementation of more adaptive and inclusive policy measures. The findings offer more profound insight into how education, migration, and labor market dynamics intersect, drawing attention to the structural barriers that influence the experiences of international students in their host countries.
Keywords: International students; Swedish labor market; legal and social barriers; job search strategies